PENGETAHUAN TENTANG KONDOM SEBAGAI UPAYA PENCEGAHAN HIV/AIDS PADA WANITA PEKERJA SEKS KOMERSIAL DI PASAR KEMBANG YOGYAKARTA - Budi Rahayu (Medika Respati : Jurnal Ilmiah Kesehatan, 2017)
Background : aquired Immune Deficiency Syndrome, or better known as AIDS is caused by the Human Deficiency Virus or HIV which attacks the immune system. Largest contributor to HIV / AIDS infection generally occurs due to sexual intercourse and multiple sexual partners at risk behavior did not use condoms. The impact of this disease can cripple the immune system and cause death, so that best effort is a preventive manner by using condoms during sexual intercourse in Hamlet Sosrowijayan Kulon is one of the largest prostitution in Yogyakarta, this gives great opportunities for HIV / AIDS if no knowledge about the importance of using condoms as one cause.Objective: This study aimed to gain knowledge about condoms as prevention of HIV / AIDS on female commercial sex workers in Pasar Kembang Jogjakarta.  Research Method: qualitative approach phenomenaligic Snowball sampling method to collect data by sampling and Indeep Interview. The number of respondents who used five oang female commercial sex workers and data analysis performed by descriptive analysisResult: general overview of knowledge about condoms as a prevention of HIV / AIDS on female commercial sex workers in Pasar Kembang, Yogyakarta, in 2010, including about knowledge of condoms, condom benefits, and how to use condoms as a prevention effort HIV / AIDS has been able to identify, understand, apply and evaluate the mean level of knowledge of women workers are very good commercial seksk but it does not affect the use of condoms at the time of serving the customer. Most customer service is a commercial sex women students so that knowledge of condoms as prevention of HIV / AIDS is very good because of their educational background is college Keyword: Knowledge of condoms, HIV / AIDS.